Wakaf Produktif dan Pemberdayaan Pesantren dalam Kitab Alfiyyah Zubad pada Mata Pelajaran Kitab di Pondok Pesantren Raudlatul Muhibbin Al-Mustainiyyah Surakarta: Productive Endowments and Empowerment of Islamic Boarding Schools in the Alfiyyah Zubad Book in Book Subjects at the Raudlatul Muhibbin Al-Mustainiyyah Islamic Boarding School in Surakarta - Amarul Wildan Ahsani; Muhammad Nur Ihrom; Muhammad Nasrul Arif; Muhammad Nawwaf Nabilun Nuha (DIRASAH: Jurnal Kajian Islam, 2025)
This study discusses the implementation of productive waqf as a means of empowering Islamic boarding schools (pesantren) in the perspective of Kitab Alfiyyah Zubad within the context of classical Islamic studies at Pondok Pesantren Raudlatul Muhibbin Al-Mustainiyyah Surakarta. The background of this research arises from the need of pesantren to optimize their economic potential through productive waqf management while maintaining the classical jurisprudential values taught in the traditional curriculum. The purpose of this study is to examine the concept of productive waqf based on the understanding of Alfiyyah Zubad and to analyze its implementation in strengthening the economic independence of the pesantren. This research employs a descriptive qualitative method using literature review and field observation on waqf practices within the institution. The findings indicate that productive waqf management enhances pesantren self-reliance, expands educational activities, and creates sustainable socio-economic impacts for students (santri) and the surrounding community. The study concludes that the concept of productive waqf aligns with the jurisprudential principles contained in Alfiyyah Zubad and serves as a strategic instrument to achieve independent and competitive Islamic educational institutions.